The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1152/ajplung.00129.2021
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study to assess the circulating renin-angiotensin system in COVID-19 acute respiratory failure

Abstract: The renin-angiotensin system (RAS) is fundamental to COVID-19 pathobiology, due to the interaction between the SARS-CoV-2 virus and the angiotensin-converting enzyme-2 (ACE2) co-receptor for cellular entry. The prevailing hypothesis is that SARS-CoV-2-ACE2 interactions lead to an imbalance of the RAS, favoring pro-inflammatory Ang II related signaling at the expense of the anti-inflammatory Ang-(1-7) mediated alternative pathway. Indeed, multiple clinical trials targeting this pathway in COVID-19 are underway.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
54
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 20 publications
(33 reference statements)
1
54
1
Order By: Relevance
“…This hypothesis is supported by the observation that, in the circulation and in the lungs, the conversion of AngII to Ang-( 1-7) is much more POP-dependent than ACE2-dependent [95]. Note, however, that in a recent investigation [93] no difference was observed between POP activity in COVID-19 patients and controls.…”
Section: Meta-analysis On Ras Components In Covid-19mentioning
confidence: 78%
See 1 more Smart Citation
“…This hypothesis is supported by the observation that, in the circulation and in the lungs, the conversion of AngII to Ang-( 1-7) is much more POP-dependent than ACE2-dependent [95]. Note, however, that in a recent investigation [93] no difference was observed between POP activity in COVID-19 patients and controls.…”
Section: Meta-analysis On Ras Components In Covid-19mentioning
confidence: 78%
“…We review here recent data about measurements of RAS components in COVID-19. For that purpose, we manually collected and screened a series of clinical and experimental results from [79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94], listed in Supplementary Table S1. The individuals enrolled in these studies were classified into two or three classes: COVID-19 patients or severe and moderate COVID-19 patients, and controls or asymptomatic patients.…”
Section: Meta-analysis On Ras Components In Covid-19mentioning
confidence: 99%
“…10 Previous pilot studies using this technique reported circulating levels of Ang II in the 20 pM range (20 pg/mL) amongst COVID-19 negative and positive patients with moderate and severe respiratory failure. 8 In contrast, Gerard et al found Ang II undetectable (<0.3 pg/mL) in the majority of their serum samples for both control and COVID19 groups, perhaps reflecting ex-vivo metabolism of Ang II in the serum samples.…”
mentioning
confidence: 85%
“…These findings may be counterintuitive to the presumed pathophysiology related to ACE2-induced endocytosis as a result of SARS-CoV-2 binding and relative imbalance favoring AngII activity relative to Ang(1-7). 8 This imbalance has been suspected of being pro-inflammatory and vasoconstrictive, perpetuating acute lung injury in patients hospitalized with SARS-CoV-2 infection. Further, while this has been thought to be unique to COVID-19 related ARDS, findings by Gerard suggest this may be ubiquitous to ARDS regardless of etiology.…”
mentioning
confidence: 99%
“…For example, it is known about the important role of the reninangiotensin-aldosterone system (RAAS), which is an integral part of the complex of blood pressure regulation and blood redistribution [28]. Currently, many researchers are considering changes in this system in patients with COVID-19 pneumonia resulting from viral aggression and are trying to find an effective correction of these deviations [29][30][31][32][33][34][35].…”
mentioning
confidence: 99%